Influence of tool rotation speeds on mechanical and morphological properties of friction stir processed nano hybrid composite of MWCNT-Graphene-AZ31 magnesium - Sanjay Sharma; Amit Handa; Sahib Sartaj Singh; Deepak Verma (Journal of Magnesium and Alloys, 2019)
The ever-increasing demand for light weighted hard materials for transportation industries encouraged researchers to develop composites with excellent mechanical properties which can transform it into more economical and eco-friendly. Reinforcing the metals with carbonaceous nanomaterials are progressively in focus due to their excellent capability to inculcate and tailor the properties of MMCs. In the present research, a hybrid nanocomposite of MWCNT-Graphene-AZ31 Mg alloy has been developed by using variable tool rotation speeds with friction stir processing (FSP). Optimized reinforcement ratio of 1.6% vol. MWCNT and 0.3% vol. of graphene have been used with variable tool rotation speeds, whereas other processing parameters are kept constant. The developed specimens were investigated using standard testing equipment for evaluating and comparing the mechanical properties on the basis of the microstructure of the processing regions and their morphological analysis, according to the ASTM standards. The obtained results revealed an improvement of 19.72% in microhardness and 77.5% of compressive strength in comparison with the base metal AZ 31 Magnesium alloy, with a tool rotational speed of 1400 rpm. The values of tensile stress and percentage area reduction were recorded as less than that of the base metal matrix, but an increasing trend has been observed in the values of both with the improvement on rotational speeds of the tool. The effectual strengthening mechanisms are analyzed on the bases of SEM images and observed that discussed and found that grain refinement strengthening is the major contributor to the strength of the nanocomposite. Keywords: MMCs (Metal Matrix composites), Friction stir processing (FSP), Multi-walled carbon nanotubes (MWCNT), Graphene Nano Particulates (GNP), Stir Zone (SZ), Thermo-mechanically affected zone (TMAZ), Heat Affected Zone (HAZ)